Пайка ZrO₂-керамики к металлу с помощью припоя серебро—медь—кислород на воздухе - Дуров, А.В. (Адгезия расплавов и пайка материалов, 2014)
Исследована возможность пайки ZrO₂-керамики к неблагородным металлам с помощью системы Ag—Cu—O на воздухе. В качестве металлической части паяного соединения опробован ряд материалов, у которых адгезия к собственному оксиду должна быть высокой. Получены паяные соединения с прочностью до 50 МПа. Досліджено можливість паяння ZrO₂-кераміки до неблагородних металів за допомогою системи Ag—Cu—O на повітрі. В якості металевої частини паяного з’єднання випробувано ряд металевих матеріалів, у яких адгезія до власних оксидів має бути високою. Отримано паяні з’єднання з міцністю до 50 МПа. Strong brazed joints of ceramic to ceramic are obtained for a long time by metal—oxygen technology but metal to ceramic joints are more interesting. As at brazing of ceramic to metal by Ag—Cu—O system on the air joints strength is obviously determined by strength of adhesion of oxygen layer on metal surface to meta as columbium was tested the metal part of brazing joint because its adhesion to own oxide have to be high. Brazed joints with strength up to 50 MPa were obtained.